Perkuatan Dinding Penahan Tanah Kantilever Beton Bertulang di Tumbak Bayuh, Badung - Bali: Strengthening of Cantilever Retaining Walls Reinforced Concrete in Tumbak Bayuh, Badung - Bali - Silvi, Ni Putu (Bentang : Jurnal Teoritis dan Terapan Bidang Rekayasa Sipil, 2024)
The research, a reinforced concrete cantilever DPT case that experienced a slope was taken. The purpose of this study is to analyze the reinforcement of reinforced concrete cantilever DPT in order to meet the requirements for its stability level. The level of stability analyzed is overturning, sliding and bearing capacity. The method used in this study is a quantitative method with the help of Geo5 software. By adding reinforced floor slabs 200 mm thick, 1500 mm wide and 2000 mm deep from the upper limit, the stability parameters against overturning, shearing and soil bearing capacity have been met. Overturning stability with a safety factor of 2.01 > 1.50 (OK), shear stability with a safety factor = 1.71 > 1.50 (OK) and soil carrying capacity stability with a safety factor of 2.01 > 2.00 (OK), where the overturning, shearing and strength stability curves bearing after reinforcement is above the allowable factor curve. The research results concluded that it was necessary to add reinforced concrete slabs for the stability of the soil retaining walls required at this location.